Role and limitations of NGOs in partnership with the state - Fontes Filho, Joaquim (Revista Estudios de Políticas Públicas, 2017)
The new paradigms of public administration are strongly based on greater interaction between the state, private sector and society through actions based on networks, co-production, and collaborative governance. However, several characteristics of civil society organizations or non-governamentals organizations (NGO) bring limitations to an effective long-term partnership. This paper aims to describe and analyze the limitations of NGOs that may affect these partnerships and the nature of this organizations, with reference to the Brazilian context, since the institutional environment and regulatory framework is critical to understand these limitations. Based on a meta analysis in former studies that assessed the relationship between NGO and the state, it was possible to point as the main problems for the NGOs from this relationships.